O‘QUVChILARNING MULOQOT MADANIYATINI AKSIOLOGIK YONDAShUVLAR ASOSIDA ShAKLLANTIRISh ZARURATI - Ibodullayeva, I. (SCIENCE and SOCIETY, 2025)
The article presents the view that the formation of a culture of communication based on axiological approaches in the educational process requires consideration of national values, customs, and traditions. Such an approach contributes to educating students in the spirit of patriotism, supports their personal and social development, and emphasizes that human life is a continuous process of evaluating events, setting goals, conducting research, drawing conclusions, and forming one’s own worldview.